Follow-up and treatment pattern during Ramadan and evaluation of the outcome of Ramadan fasting on clinical, biochemical and metabolic parameters in patients with type 2 diabetes mellitus: a realworld, multi-center, prospective observational study (BIRDEM Medical Journal, 2020)
Background: There are variable effects of Ramadan fasting on clinical and biochemical variables of diabetic people. Anti-diabetic agents are often adjusted during this time to reflect changes in lifestyle. The study was conducted to understand the diversity of follow-up, treatment pattern, clinical, and biochemical outcome of Ramadan fasting among type 2 diabetic patients who observed Ramadan fast.Methods: This real-world, multi-center, prospective, observational study was conducted at the diabetes outpatient department of National Healthcare Network (NHN) Uttara Center of Bangladesh Diabetic Somity (BADAS), Dhaka, Bangladesh and outpatient department of MARKS Hormone and Diabetes clinic, MARKS Medical College &Hospital in Dhaka, Bangladesh upon randomly selected type 2 diabetic patients, recruited 1 to 12 weeks prior to the Ramadan and followed up till 12 weeks post-Ramadan period. Finally, a total of 271 participants completed satisfactory follow up. Data was collected before, during, and after Ramadan using a set of questionnaires in a face to face interview.Results: The majority (80.1%) of participants received pre-Ramadan education, counseling, adjustment of medication and other direction to help them cope with Ramadan fasting. A significant reduction of weight, body mass index (BMI)) and blood pressure were reported after Ramadan fast (p